Principles of Renal Function Measurement (Limitations of Gotch's Kt/V). Issue 1 (30th May 2018) - Bonert, Michael; Saville, Bradley A.
Kt/V is a nondimensional number and a scaling parameter that has, with arbitrary definitions, been recast as a measure of dialysis by Gotch and Lysaght. This editorial discusses the concept of nondimensional numbers within the context of dialysis measurement, modeling, and medical evidence. It concludes that Gotch's Kt/V, Lysaght's Kt/V, and standardized Kt/V are not well suited to measure dialysis. An ideal dialysis measure would be proportional to toxins cleared by the kidney, portable with regard to dialysis modality, practical (largely devoid of calculations) and reflective of the pathology/physiology.